2017
DOI: 10.3390/md15110346
|View full text |Cite
|
Sign up to set email alerts
|

AS1041, a Novel Synthesized Derivative of Marine Natural Compound Aspergiolide A, Arrests Cell Cycle, Induces Apoptosis, and Inhibits ERK Activation in K562 Cells

Abstract: AS1041 is a novel synthesized anthraquinone lactone derivative of marine natural compound aspergiolide A (ASP-A) with new structure skeleton and marked cytotoxicity in cancer cells. To study its cytotoxicity in detail, we evaluated its activity on human K562 chronic myelogenous leukemia cells and investigated the related molecule mechanisms. AS1041 significantly inhibited the proliferation and colony formation of K562 cells. Moreover, AS1041 arrested cell cycle progression at G2/M phase in a concentration-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…AS1041 showed half maximal inhibitory concentrations (IC50) ranging from 1.56 to 10.30 µM against chronic myelogenous leukemia cells (K562), promyelocytic leukemia cells (HL-60), acute T lymphocytic leukemia cells (Kasumi-1), T lymphocytic leukemia (Jukrat cells), cervical carcinoma (HeLa cells), cervical cancer cell lines CaSki, hepatocellular carcinoma (BEL-7402), lung cancer cells (A549), breast cancer cells (MDA-MB-231), and prostate cancer cells (PC-3), with K562 cells being the most sensitive to AS1041. Subsequent experiments revealed that AS1041 inhibited the proliferation of K562 in a concentration- and time-dependent manner, induced cell cycle arrest at the G2/M checkpoint, and induced a non-caspase-dependent apoptosis [ 281 ].…”
Section: Marine Fungimentioning
confidence: 99%
“…AS1041 showed half maximal inhibitory concentrations (IC50) ranging from 1.56 to 10.30 µM against chronic myelogenous leukemia cells (K562), promyelocytic leukemia cells (HL-60), acute T lymphocytic leukemia cells (Kasumi-1), T lymphocytic leukemia (Jukrat cells), cervical carcinoma (HeLa cells), cervical cancer cell lines CaSki, hepatocellular carcinoma (BEL-7402), lung cancer cells (A549), breast cancer cells (MDA-MB-231), and prostate cancer cells (PC-3), with K562 cells being the most sensitive to AS1041. Subsequent experiments revealed that AS1041 inhibited the proliferation of K562 in a concentration- and time-dependent manner, induced cell cycle arrest at the G2/M checkpoint, and induced a non-caspase-dependent apoptosis [ 281 ].…”
Section: Marine Fungimentioning
confidence: 99%
“…Cell viability was measured by the SRB assay [73]. Briefly, cells were seeded onto 96-well plates (0.3 × 10 4 -0.7 × 10 4 cells/well) and allowed to attach for 24 h, TCN was added to the medium at various concentrations for 72 h. Cold trichloroacetic acid (10%) was added and cells were fixed at 4 • C for 1 h, then washed with deionized water five times and dried in air.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…We also found that compound 7bb , in which the hydroxyl group transferred from C-20 to C-12 compared with 8ae′ , showed even more potential inhibitory activity with an IC 50 values ranged from 1.6 to 7.5 μM, which is comparable to the natural product 1a . In addition, further detailed pharmacological studies showed that 7bb has a novel antitumor mechanism of inhibiting ERK activation in K562 cells . The cytotoxicity suggested that the promising cytotoxic activity correlated with both of the methoxy group at the C-22 position and hydroxyl group at the C-12 or C-20 position.…”
mentioning
confidence: 97%
“…In addition, further detailed pharmacological studies showed that 7bb has a novel antitumor mechanism of inhibiting ERK activation in K562 cells. 10 The cytotoxicity suggested that the promising cytotoxic activity correlated with both of the methoxy group at the C-22 position and hydroxyl group at the C-12 or C-20 position. Furthermore, it seems that the analogues with hydroxyl group at the C-12 were more potent than the counterparts of the C-20 position.…”
mentioning
confidence: 99%